2021
DOI: 10.3389/fpsyt.2021.755159
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Rumination and Negative Affect in the Effect of Mind-Wandering on Symptoms in Patients With Obsessive-Compulsive Disorder

Abstract: To explore the relationship between negative affect, mind-wandering, rumination and obsessive-compulsive symptoms, 100 patients with obsessive-compulsive disorder and 100 healthy controls were assessed using the Obsessive-Compulsive Inventory, the Beck Anxiety Inventory, the Beck Depression Inventory, the Mind Wandering Scale and the Ruminative Response Scale. The results show that (i) patients diagnosed with obsessive-compulsive disorder displayed higher obsessive-compulsive symptoms, negative affect, mind-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…For example, a long time and intense mental pursuits spent on obsessions and compulsions in patients with OCD may reduce the capacity for basic cognitive processes, impact time management and concentration, cause a slower reaction/movement and getting lost in thoughts, which are also seen in CDS (Fitzgerald et al, 2021; Shin et al, 2014; Stern et al, 2017). Furthermore, given the potential associations of both OCD and CDS with mind-wandering (Becker & Barkley, 2021; Fredrick et al, 2020; Seli et al, 2017; Wang et al, 2021), similar behavioral symptoms (e.g., not paying attention to the surrounding environment) may be seen in both conditions as a reflection of different internal states that are difficult to differentiate. That is, in both cases, people may be internally focused because they are mind-wandering, worrying, ruminating, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a long time and intense mental pursuits spent on obsessions and compulsions in patients with OCD may reduce the capacity for basic cognitive processes, impact time management and concentration, cause a slower reaction/movement and getting lost in thoughts, which are also seen in CDS (Fitzgerald et al, 2021; Shin et al, 2014; Stern et al, 2017). Furthermore, given the potential associations of both OCD and CDS with mind-wandering (Becker & Barkley, 2021; Fredrick et al, 2020; Seli et al, 2017; Wang et al, 2021), similar behavioral symptoms (e.g., not paying attention to the surrounding environment) may be seen in both conditions as a reflection of different internal states that are difficult to differentiate. That is, in both cases, people may be internally focused because they are mind-wandering, worrying, ruminating, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that the type and extent of OCD symptoms are predicted by the frequency of spontaneous, but not deliberate, mind-wandering experiences (Cole & Tubbs, 2022; Seli et al, 2017). It has been revealed that mind-wandering confers an increase in obsessive-compulsive thoughts and the severity of obsessive-compulsive symptoms is positively associated with excessive mind-wandering (Seli et al, 2017; Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Those individuals who exhibit high rumination are more likely to have more severe OCS. 21 , 22 Additionally, the specific emotional processing style of frequent procrastinators may exacerbate OCS. They cannot be self-compassionate and are prone to generating more negative emotions when experiencing failure.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of rumination is to reduce emotional distress (Shaaban, 2020). Rumination can increase anxiety and stress levels, eventually setting the stage for depression (Bagherinezhad et al, 2010;McEvoy et al, 2013;Polat & Asi Karakaş, 2021;Ruscio et al, 2015;Wang et al, 2021). In such situations, the individual will be unable to overcome conflicts and tensions arising from pressures and stresses, thereby losing control over self-management and life (Polat & Asi Karakaş, 2021;Simpson & Papageorgiou, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In such situations, the individual will be unable to overcome conflicts and tensions arising from pressures and stresses, thereby losing control over self-management and life (Polat & Asi Karakaş, 2021;Simpson & Papageorgiou, 2003). Research indicates that symptoms of psychosomatic diseases like headaches, stomach and intestinal complaints, or digestive problems, and many chronic diseases like obesity, diabetes, hypertension, cardiovascular diseases, and obesity are influenced by rumination (Murray et al, 2021;Polat & Asi Karakaş, 2021;Rezaei et al, 2015;Torfiamidpoor et al, 2022;Wang et al, 2022;Wang et al, 2021). Cognitive underpinnings of emotional disorders such as depression, obsessive-compulsive disorder, generalized anxiety, and post-traumatic stress disorder are observed, which can often be precursors to obesity (Ahmadboukani et al, 2022;Bagherinezhad et al, 2010;Boger et al, 2020;Cludius et al, 2020;Pugach et al, 2020;Raines et al, 2017; O Rezaei et al, 2015;Ruscio et al, 2015;Sangani & Dasht Bozorgi, 2018;Tanhadoust et al, 2021;Wang et al, 2021;Watkins & Nolen-Hoeksema, 2014).…”
Section: Introductionmentioning
confidence: 99%